Question

The deflection of a beam, y(x), satisfies the differential equation 8 * d 4y dx4   =  w(x)    on  0  ...

The deflection of a beam, y(x), satisfies the differential equation

8 *
d 4y
dx4

  =  w(x)    on  0  <  x  <  1.

Find y(x) in the case where w(x) is equal to the constant value 38, and the beam is embedded on the left (at x  =  0) and simply supported on the right (at x  =  1).

Please Calculate all the constant in equation

Homework Answers

Know the answer?
Your Answer:

Post as a guest

Your Name:

What's your source?

Earn Coins

Coins can be redeemed for fabulous gifts.

Not the answer you're looking for?
Ask your own homework help question
Similar Questions
26. Find the solution of the differential equation. y'' +4y' +4y =0 ; y(-1)=2 and y'(-1)=-1
26. Find the solution of the differential equation. y'' +4y' +4y =0 ; y(-1)=2 and y'(-1)=-1
Find a series solution for the differential equation 4y'+ y = 0
Find a series solution for the differential equation 4y'+ y = 0
Solve the following differential equations y''-4y'+4y=(x+1)e2x (Use Wronskian) y''+(y')2+1=0 (non linear second order equation)
Solve the following differential equations y''-4y'+4y=(x+1)e2x (Use Wronskian) y''+(y')2+1=0 (non linear second order equation)
Solve the differential equation by UC Method. Do not evaluate the exact value of coefficients. y^'''+y^''-4y^'-4y=8x+8+6e^-x
Solve the differential equation by UC Method. Do not evaluate the exact value of coefficients. y^'''+y^''-4y^'-4y=8x+8+6e^-x
Power series Find the particular solution of the differential equation: (x^2+1)y"+xy'-4y=0 given the boundary conditions x=0,...
Power series Find the particular solution of the differential equation: (x^2+1)y"+xy'-4y=0 given the boundary conditions x=0, y=1 and y'=1. Use only the 7th degree term of the solution. Solve for y at x=2. Write your answer in whole number.
find the solution of the Differential equation 4y''-y=xe^(x/2)
find the solution of the Differential equation 4y''-y=xe^(x/2)
Find the general solution to the differential equation: y’’ – 6 y’ + 13y = 0...
Find the general solution to the differential equation: y’’ – 6 y’ + 13y = 0 Find the general solution to the differential equation: y’’ + 5y’ + 4y = x + cos(x)
x^2y'' − 3xy'+ 4y = 0 ; y(1)=5 y'(1)=3 differential equation using the Cauchy-Euler method
x^2y'' − 3xy'+ 4y = 0 ; y(1)=5 y'(1)=3 differential equation using the Cauchy-Euler method
x^2y'' − 3xy'+ 4y = 0 ; y(1)=5 y'(1)=3 differential equation using the Cauchy-Euler method
x^2y'' − 3xy'+ 4y = 0 ; y(1)=5 y'(1)=3 differential equation using the Cauchy-Euler method
Solve the following differential equation using taylor series centered at x=0: (2+x^2)y''-xy'+4y = 0
Solve the following differential equation using taylor series centered at x=0: (2+x^2)y''-xy'+4y = 0
ADVERTISEMENT
Need Online Homework Help?

Get Answers For Free
Most questions answered within 1 hours.

Ask a Question
ADVERTISEMENT